From Ethnoscience to Digital Inquiry: Mapping Research Trends and Gaps in Critical Thinking and Digital Literacy within STEM Education - Prelia Dwi Amanah; Agus Abhi Purwoko; Agus Ramdani; Stefanie Astrid Aipassa (FKIP Universitas Lampung, 2026)
The integration of ethnoscience, digital technology, and inquiry-based learning in STEM education has become an increasingly important focus in science education research. This systematic literature review aims to map research trends, identify effective models, and reveal gaps related to critical thinking skills and digital literacy in STEM-based science learning. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method, 101 articles published from 2010 to 2026 were selected from Scopus (Q1–Q3) and SINTA (S1–S2) indexed journals. Data from Dimensions AI (4,095 total publications, 2017–2026) and VOSviewer bibliometric mapping (232 items, 5 clusters) further contextualize the research landscape. The analysis reveals five dominant themes: (1) Ethno-STEM and project-based learning, (2) augmented and virtual reality in science learning, (3) development of critical thinking skills through inquiry-based approaches, (4) digital literacy in education, and (5) innovative STEM learning models. The findings indicate that inquiry-based approaches, when combined with local cultural integration (ethnoscience) and digital technology, are effective in improving students' critical thinking skills. However, research on the integrated development of a specific model that simultaneously addresses ethnoscience, digital inquiry, and STEM remains limited. This study provides a theoretical foundation for developing an innovative learning model that bridges local cultural wisdom with 21st-century digital competencies. Keywords: critical thinking, digital literacy, ethnoscience, inquiry-based learning, STEM education.